Dergaon Meteorite: A Preliminary Geochemical Investigation. - MAJUMDAR, DILIP; DUTTA, SUNIL; K. GOGOI, PRADIP; SONOWAL., JUTHIKA (Asian Journal of Chemistry, 2010)
A preliminary investigation of Dergaon meteorite has been undertaken for selective chemical composition of Fe, AI, Si, Cu, Mn and P and abundance of opaque and non-opaque mineral constituents in it Preliminary petrographic investigations suggested that the Dergaon meteorite belongs to the chondritic class, having primary silicate minerals like olivine, pyroxene, minor plagioclase feldspar and glassy groundmass containing small droplets of iron and troilite. Opaque minerals mostly comprise of troilite, kamacite, taenite, schreibersite, chalcopyrite with minor cohenite, sphalerite, graphite and pyrite. Chemical analysis revealed that the meteorite is composed mainly of silicates (57.69%), iron (32.8%) and phosphorus (1.04%). Volumetric estimate by modal analysis roughly conforms the chemical data.